(3HZjI GdYdeGA hGdQhGI aj GdPjd Ydi cJGH TjNi aj GdbVGIs - (3TeS GdOjf CHi GdNjQ eMeO Hf YHO GdQMef Hf eMeO Hf CHi HcQ Hf YKeGf GdSNGhis; (3GHf MLQ GdYSbdGfj,J (B852 (3g` s ((3CMeO Hf CHj HcQ GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GdMce GdYOd s
(3BNQgG (B:s
(3hhGab GdaQGZ ef cJGHJg ai jhe GdKdGKGA QGHY YTQ ef ThGd s
(3ghPjd Ydi cJGH QaY GdEUQ dTjNg GHf MLQs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs